Results are out! Find what you need...fast. Get quick advice or join the chat
x

Unlock these great extras with your FREE membership

  • One-on-one advice about results day and Clearing
  • Free access to our personal statement wizard
  • Customise TSR to suit how you want to use it

Translations of graphs need help

Announcements Posted on
Rate your uni — help us build a league table based on real student views 19-08-2015
  1. Offline

    ReputationRep:
    Can someone reflect these in the y-axis please?

    y=2x^3+x^2-5x+1

    y=3sin(x)

    And can someone stretch these parallel to the x axis please

    y=x^2 by scale factor 3 parallel to the x-axis

    y=x^2-4x+1 by scale factor 0.5 parallel to the x axis

    y=3sin(x) by scale factor 1/5 parallel to the x-axis

    45 minutes ago
    - 4 days left to answer.
  2. Online

    ReputationRep:
    A reflection in the y axis is to swap around the positive and negative sides of the x axis.

    To stretch f(x) by a factor of a along the x axis, you need f(x) to come at a*x, hence you get the stretch being f(x/a). The division by a means x has to be a times as large to get the same value of f.
  3. Offline

    ReputationRep:
    agree to that ^^^^^
  4. Offline

    ReputationRep:
    (Original post by iceman95)
    Can someone reflect these in the y-axis please?

    y=2x^3+x^2-5x+1

    y=3sin(x)

    And can someone stretch these parallel to the x axis please

    y=x^2 by scale factor 3 parallel to the x-axis

    y=x^2-4x+1 by scale factor 0.5 parallel to the x axis

    y=3sin(x) by scale factor 1/5 parallel to the x-axis

    45 minutes ago
    - 4 days left to answer.
    Generally:
    let y=f(x)
    THen
    Reflection in the y-axis: y=f(-x)
    Reflection in the x-axis:y=-f(x)
    Translating by 'a' parallel to the x: y=f(x-a)
    Translating by 'a' parallel to the y: y=f(x)+a
    Streching by scale factor 'a' parallel to x: y=f(\frac{1}{a}x)
    Streching by scale factor 'a' parallel to y: y=a\cdot f(x)

    F.e for 2nd
    y=sin3x \rightarrow y=sin(-3x)=-sin3x
    for 4th
    y=x^2-4x+1 \rightarrow y=\left (2x)^2-4(2x)+1=4x^2-8x+1
  5. Offline

    ReputationRep:
    (Original post by ztibor)
    Generally:
    let y=f(x)
    THen
    Reflection in the y-axis: y=f(-x)
    Reflection in the x-axis:y=-f(x)
    Translating by 'a' parallel to the x: y=f(x-a)
    Translating by 'a' parallel to the y: y=f(x)+a
    Streching by scale factor 'a' parallel to x: y=f(\frac{1}{a}x)
    Streching by scale factor 'a' parallel to y: y=a\cdot f(x)

    F.e for 2nd
    y=sin3x \rightarrow y=sin(-3x)=-sin3x
    for 4th
    y=x^2-4x+1 \rightarrow y=\left (2x)^2-4(2x)+1=4x^2-8x+1
    How can I reflect y=2x^3+x^2-5x+1 into the y-axis?

Reply

Submit reply

Register

Thanks for posting! You just need to create an account in order to submit the post
  1. this can't be left blank
    that username has been taken, please choose another Forgotten your password?
  2. this can't be left blank
    this email is already registered. Forgotten your password?
  3. this can't be left blank

    6 characters or longer with both numbers and letters is safer

  4. this can't be left empty
    your full birthday is required
  1. By joining you agree to our Ts and Cs, privacy policy and site rules

  2. Slide to join now Processing…

Updated: May 3, 2012
TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

New on TSR

Rate your uni

Help build a new league table

Poll
How do you read?
Study resources
Quick reply
Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.